Decreased MIP-3α Production from Antigen-Activated PBMCs in Symptomatic HIV-Infected Subjects - Fuchun Zhang; Lingling Sun; Mark K. Lafferty; Joseph B. Margolick; Alfredo Garzino-Demo (Pathogens, 2021)
CD4+ CCR6+ T cells are highly susceptible to HIV infection, and a high cytokine producing CCR6+ T cell subset is selectively lost during HIV infection. The CCR6 chemokine MIP-3α (CCL20) is produced at sites of infection in SIV animal models. Recently, we have shown that MIP-3α inhibits HIV replication. This inhibition of HIV infection is mediated by CCR6 signaling and eventuates in increased APOBEC3G expression. Since there are few existing reports on the role of MIP-3α in health or disease, we studied its production by PBMCs from HIV-seronegative and HIV+ subjects. We evaluated the ability of PBMCs to produce MIP-3α in response to antigen stimulation using cells obtained from two groups: one composed of HIV-seronegative subjects (n = 16) and the other composed of HIV+ subjects (n = 58), some asymptomatic and some with clinically defined AIDS. Antigens included fragment C of the tetanus toxin, Candida albicans, whole-inactivated HIV, and HIV p24. MIP-3α was detected by ELISA in tissue culture supernatants of antigen-stimulated PBMCs. MIP-3α production by antigen-stimulated PBMCs was readily measured for HIV-negative subjects and for HIV-seropositive asymptomatic subjects, but not for patients with AIDS. These results suggest that subversion of the MIP-3α-CCR6 axis by HIV during the course of infection contributes to the loss of immune function that eventually leads to AIDS.